2021
DOI: 10.3390/s21217421
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Atmosphere-Regolith Water Cycle on Present-Day Mars

Abstract: The water content of the upper layers of the surface of Mars is not yet quantified. Laboratory simulations are the only feasible way to investigate this in a controlled way on Earth, and then compare it with remote and in situ observations of spacecrafts on Mars. Describing the processes that may induce changes in the water content of the surface is critical to determine the present-day habitability of the Martian surface, to understand the atmospheric water cycle, and to estimate the efficiency of future wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Previous analysis of the vertical profile at arctic Martian regions suggests that during spring and summer, a large percentage of the water column (> 25% and up to nearly 100%) was confined below ~ 2.5 km 47 . These results are comparable to those provided by the REMS instrument package on the Curiosity rover at Gale crater 24 and are consistent with previous research based on orbital and in-situ observations and modelling 44 , 48 54 . We conclude that similarly to what happens on other sites on Mars 55 , there is a strong rock and regolith-atmosphere exchange mechanism on Mars 56 , likely owing to the combination of adsorption–desorption of water on the regolith grain surfaces and to hydration-dehydration of salts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous analysis of the vertical profile at arctic Martian regions suggests that during spring and summer, a large percentage of the water column (> 25% and up to nearly 100%) was confined below ~ 2.5 km 47 . These results are comparable to those provided by the REMS instrument package on the Curiosity rover at Gale crater 24 and are consistent with previous research based on orbital and in-situ observations and modelling 44 , 48 54 . We conclude that similarly to what happens on other sites on Mars 55 , there is a strong rock and regolith-atmosphere exchange mechanism on Mars 56 , likely owing to the combination of adsorption–desorption of water on the regolith grain surfaces and to hydration-dehydration of salts.…”
Section: Discussionsupporting
confidence: 91%
“…The plausible existence of brines or salt hydrates on the surface or subsurface has several implications for Mars's past and current habitability. Experiments in simulation chambers have shown that for certain temperature and a w conditions, Mg, Ca, and Na perchlorates and sulfates can hydrate or deliquesce, forming stable liquid brines under present-day Martian conditions [22][23][24] . The Planetary Instrument for X-Ray Lithochemistry (PIXL) and the Scanning Habitable Environments with Raman and Luminescence for Organics and Chemicals (SHERLOC) instruments have investigated the abrasion patches and found hygroscopic and deliquescent salts such as Mg, Fe (hydrated) and Ca sulfates (anhydrite mostly), chlorides and perchlorates (Initial Reports-PDS; [25][26][27][28] ).…”
mentioning
confidence: 99%
“…Water may also be absorbed to grain boundaries. Recent experiments with regolith simulant have demonstrated that a mixture containing 10 wt% ferric sulfate can absorb as much as 18% of its weight in water, and a mixture containing 10 wt% calcium chloride can absorb as much as 50% of its weight in water (Ramachandran et al., 2021). In these experiments, this water absorption changes the cohesiveness of fine regolith particles, forming granular structures.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the active ground patterns have broad implications for diverse geomorphic processes on Mars. Our work adds to a set of studies of a present‐day active atmosphere‐regolith water cycle (e.g., Bishop et al., 2021; Chevrier & Rivera‐Valentin, 2014; Martín‐Torres et al., 2015; Schmidt et al., 2017; Vakkada Ramachandran et al., 2021; Wang et al., 2019). Collectively, this research suggests that the surface of Mars is currently being shaped by environmentally driven volumetric changes of the near‐surface bedrock, as well as eolian, impact, insolation, and gravitational processes.…”
Section: Introductionmentioning
confidence: 86%